The weatherman. Vol. 2 - Leheup, Jody; Leheup, Jody; Fox, Nathan (Image Comics, 2020)
"Mars' wise-cracking, hard partying local weatherman Nathan Bright has no memory of his alleged role in the terrorist attack that killed 18 billion people. But that isn't stopping him from trying to atone for the actions of his past self. Hunted by literally everyone in the galaxy, Nathan's quest takes him to the scene of the crime -- Earth -- where he continues his search for redemption and the key to saving humanity from another extinction-level attack. He's about to discover that some truths are better left unknown, and Earth's not lifeless at all... it's MONSTROUS!" --